Efektivitas Teknik Psikologi Selling dalam Meningkatkan Penjualan dengan Komitmen Pelanggan sebagai Variabel Intervening: Studi pada Industri E-Commerce di Indonesia - Rajagukguk, Frederick Rudy Sentosa; Harahap, Hastuti Handayani; Arifin, Indra Welly; Hutajulu, Lija Romauli; Juanda, Ahmad (STIE Bina Karya, 2025)
This study aims to examine the effectiveness of Psychological Selling Techniques in increasing sales with Customer Commitment as an intervening variable in the e-commerce industry in Indonesia. The research method employed is quantitative, analyzed using Smart PLS. The results indicate that Psychological Selling Techniques significantly influence both Customer Commitment and Sales Increase. Furthermore, Customer Commitment significantly mediates the effect of Psychological Selling Techniques on Sales Increase. These findings suggest that implementing psychological techniques in selling can enhance customer loyalty and sustainable sales growth. This study offers practical implications for e-commerce companies to integrate psychological selling techniques into their marketing strategies to strengthen customer relationships and improve sales performance.